Has Latin America achieved universal health coverage yet? Lessons from four countries - Ramiro E. Gilardino; Pilar Valanzasca; Susan B. Rifkin (BMC, 2022)
Highlights This review presents the current situation of UHC implementation in Argentina, Brazil, Colombia, and Mexico, using different elements from the WHO in their 13th Program of Work to compare service coverage and financial protection. During the 1990s, health systems within several Latin American countries, anticipating to Universal Health Coverage increasing the service coverage, but struggling to fulfill financial protection standards. Still the four countries struggle to find mechanisms that could increase pooling mechanisms capable of increasing service coverage, while reducing financial inequities among people. The decentralization of the primary healthcare system, the development of public-private partnerships, and the implementation of progressive financing mechanisms like conditional cash transfers are potential manners to improve service delivery and financial protection contributing to effective UHC.